Integrasi Dow Jones Islamic Market-5 Dengan Indeks Saham Syariah Indonesia - Soeharjoto Soekapdjo (ITB AAS INDONESIA Surakarta, 2021)
Sharia capital market plays a role in supporting economic growth in Indonesia. However, Indonesian Sharia Stock Index development is integrated with the Dow Jones Islamic Market-5. Aims of this research is to find out Dow Jones Islamic Market-5 influence on the Indonesian Sharia Stock Index. This study used Islamic stock index monthly time series data in 2016-2020, from Indonesia and Dow Jones Islamic Market in America, India, Japan, Malaysia, and Arabia. Used regression method with the Error Correction Model. Results showed that at the long or short term, Dow Jones Arabia Titans 50 Index and Dow Jones Islamic Market Asia or Pacific ex-Japan Index and at the long term for Dow Jones Islamic Market India Index had a positive and significant effect on the Indonesian Sharia Stock Index. In the long run, Dow Jones Islamic Market World Index and Dow Jones Malaysia Titans 25 Index have a negative and significant effect on the Indonesian Sharia Stock Index. But in the short term, Dow Jones Islamic Market World Index, Dow Jones Islamic Market India Index, and Dow Jones Malaysia Titans 25 Index have no effect on the Indonesian Sharia Stock Index. In addition to paying attention to the integration, participants of capital market need to be aware to the occurrence of macroeconomic turmoil that results of exchange rate instability which is the main cause of economic recession in the world.